Tratamiento farmacológico de la depresión en cáncer - Bernal García, Patricia; Muñoz Algar, María José (Psicooncología, 2017)
Objective: Major depression is one of the most prevalent diagnosis in oncological patients. In Spain, about 16-49% of patients develop a major depressive disorder. When the depressive symptoms interfere with the oncological patient´s functionality, the antidepressant are the first line treatment. The objective of the present study is to analyze the effectiveness of different pharmacological options used for depression in oncological patients.Method: We performed a bibliographic review in pubmed database with the terms: . We analyzed 36 scientific articles with a clinical trial design. Results: we have found the inhibitors selective serotonin reuptakes (ISSR) are effective in treating depression in cancer patient. paroxetine is one of the most effective. The dual antidepressants also have shown efficacy for its speed of action and their utility in side symptoms like vasomotor symptoms and pain. Mirtazapine is useful to treat pain, sickness, insomnia and anxiety.Conclusion: the election of medication must be based on the symptoms profile of patient, the potential benefit, tolerability and risk/benefits with the purpose of design a strategy for each patient. The drugs most effective and tolerable in our study have been the ISSR, the mirtazapine and the dual action antidepressants.
Keywords: Depression; treatment; cancer; antidepressant; serotonin.